OPTIMALISASI MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PENERAPAN APLIKASI PEMBELAJARAN BERBASIS KAHOOT! - Ihsani, Mustofa Haris; Saidah, Zahrotus; Nuryadien, Mahbub (Wahana Islamika Jurnal Studi Keislaman, 2024)
Digital generation students grew up with technology as an integral part of everyday life. They have a very different learning style from previous generations. This research aims to answer the challenges of educators in meeting the changing learning characteristics of students in the digital era by describing the process of developing the Kahoot! and its application to learning Islamic Education, so that it can optimize students' learning motivation. The research method used is the sequential mixed method. The data collection technique uses observation, interviews, questionnaires and documentation methods using data reduction analysis, data presentation and verification. For quantitative data analysis using the Normality Test and Independent Sample T-Test. The results of this research are the development of the Kahoot! and implementation strategies in learning, as well as showing an increase in students' learning motivation after this application was implemented. This research recommendation is intended as a reference for developing Isalmic education learning applications and to provide a variety of interesting learning atmospheres for students so as to foster interest in learning and high learning motivation.